A thermal extension and loss model for Tellinen's hysteresis model. Issue 2 (25th June 2020) - Kühn, Jan; Bartel, Andreas; Putek, Piotr
Abstract : Purpose: The thermally extended Tellinen model (Kühn et al., to appear) is here investigated and equipped with a hysteresis loss model, while preserving its simple structure. Design/methodology/approach: As in the original model, these approaches are based upon phenomenal observations and measured saturation curves. The authors start with the original model and step-by-step add their extensions, such that in the end they can apply the extended model in a finite element method (FEM) simulation. During the process, care is taken to ensure that the applicability in a FEM simulation is not impaired, in terms of memory requirements and computing power. Findings: In comparison to the original model, this extended model needs some further requirements and so is a little bit more limited in its application. It is in itself coherent and well defined. The authors provide an on-the-fly algorithm computation of hysteresis losses. First numerical results for a coupled field/thermal system show expected behavior. Originality/value: The original model (Tellinen, 1998) does not take temperature into account. It includes a model for calculating hysteresis losses, but it differs largely from the approach presented here. The thermal extension is now also equipped with an on-the-fly method for hysteresis losses. Furthermore, the authors provide some analysis of simple, stable loops.